Role of endothelium-derived nitric oxide in the bleeding tendency of uremia. - Remuzzi, G; Perico, N; Zoja, C; Corna, D; Macconi, D; Viganò, G (The Journal of Clinical Investigation, 1990)
Endothelium-derived relaxing factor, now identified as nitric oxide (NO), is a labile humoral agent formed by vascular endothelial cells from L-arginine. NO mediates the action of substances that induce endothelium-dependent relaxation and plays a role in regulating blood pressure. In this study we investigated whether NO is involved in the pathogenesis of the bleeding tendency associated with renal failure. Rats with extensive surgical ablation of renal mass develop renal insufficiency due to progressive glomerulosclerosis. Like uremic humans, rats with renal mass reduction and uremia have a bleeding tendency that manifests itself by a prolonged bleeding time. We found that N-monomethyl-L-arginine (L-NMMA), a specific inhibitor of NO formation from L-arginine, completely normalized bleeding time when given to uremic rats. L-NMMA injection also increased ex vivo platelet adhesion but did not affect ex vivo platelet aggregation induced by adenosine diphosphate, arachidonic acid, and calcium ionophore A23187. The shortening effect of L-NMMA on bleeding time was completely reversed by giving the animals the NO precursor L-arginine, but not D-arginine, which is not a precursor of NO. It thus appears that NO is a mediator of the bleeding tendency of uremia.